1979
DOI: 10.1056/nejm197903083001003
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Impaired Splenic Function in Patients with Nephritis or Vasculitis (or Both) by Plasma Exchange

Abstract: By studying the clearance of autologous labeled antibody-coated or heat-damaged erythrocytes, we showed that reversible blockade of the splenic component of reticuloendothelial function existed in 14 of 15 patients referred for treatment of nephritis or vasculitis. In 10 patients treated by plasma exchange--alone in three and combined with steroids and cytotoxic drugs in six--reversal of splenic blockade followed in nine, and in the three patients treated solely by plasma exchange this reversal was demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
0
4

Year Published

1979
1979
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(80 citation statements)
references
References 9 publications
3
73
0
4
Order By: Relevance
“…In addition, recent studies suggest that variations in reticuloendothelial function also influence Fc receptormediated immune clearance. Patients with systemic lupus erythematosus (8), nephritis (9), vasculitis (9), or Sj6gren's syndrome (10) sequester and destroy erythrocytes coated with IgG antibody in their spleen more slowly than normal volunteers. This reduction in Fc receptor function may be a primary disorder contributing to tissuie damage in these (liseases (8,10) or may be duie to interference with Fc receptor function by immune complexes containinig IgG (9,11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, recent studies suggest that variations in reticuloendothelial function also influence Fc receptormediated immune clearance. Patients with systemic lupus erythematosus (8), nephritis (9), vasculitis (9), or Sj6gren's syndrome (10) sequester and destroy erythrocytes coated with IgG antibody in their spleen more slowly than normal volunteers. This reduction in Fc receptor function may be a primary disorder contributing to tissuie damage in these (liseases (8,10) or may be duie to interference with Fc receptor function by immune complexes containinig IgG (9,11).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with systemic lupus erythematosus (8), nephritis (9), vasculitis (9), or Sj6gren's syndrome (10) sequester and destroy erythrocytes coated with IgG antibody in their spleen more slowly than normal volunteers. This reduction in Fc receptor function may be a primary disorder contributing to tissuie damage in these (liseases (8,10) or may be duie to interference with Fc receptor function by immune complexes containinig IgG (9,11). In the following studies in vitro, we demonstrate that complexes containing IgG can reversibly reduce Fc receptor function of human monocytes, and that this process proceeds by an energy-dependent step(s) to the irreversible loss ofreceptor function.…”
Section: Introductionmentioning
confidence: 99%
“…Delayed clearance of IgG-coated red blood cells has been found in patients with SLE (12,13), but in patients with MCG this has been found only in those with renal disease (14). A possible rationale for the use of plasmapheresis is the observation by Lockwood et a1 (12) that plasmapheresis alone or with steroid and immunosuppressive therapy enhanced the clearance of immune complexes by the spleen in patients with nephritis and/ or vasculitis. This resulted in unexpectedly marked and often prolonged improvement even after plasmapheresis is stopped.…”
Section: Discussionmentioning
confidence: 99%
“…Immune complexes have been detected in the sera of patients with diffuse proliferative gloimierulonephritis, lupus nephritis, membranoproliferative glomerulonephritis, and other forms of nephritis (22)(23)(24). Studies of reticuloendothelial function in some ofthese forms of human renal disease have also shown impaired splenic clearance ofimmune complexes in these patients (25,26). It is uncertain if this impairment is a primary defect, or ifit is a reflection of saturation of the reticuloendothelial system by the complexes (of interest, studies of Finbloom and Plotz (27) and by Knutson et al (28) have shown that the ability of NZB/W female mice to clear soluble immune complexes was unimpaired).…”
Section: Discussionmentioning
confidence: 99%